PENGARUH KOMUNIKASI DAN MOTIVASI TERHADAP SEMANGAT KERJA KARYAWAN PADA DISINI LUXURY SPA AND VILLAS SEMINYAK - Kadek Yulia Purnitasari; Dewiwati Sujadi (Journal Research of Management, 2022)
This research aims to find out the influence of communication on employee morale at Disni Luxury Spa And Villas Seminyak. To find out the effect of motivation on employee morale at Disini Luxury Spa And Villas Seminyak. To find out how big the influence of communication and motivation on employee morale at Disini Luxury Spa And Villas Seminyak. To find out which independent variables have a dominant influence on employee morale at Disini Luxury Spa And Villas Seminyak. The sample used was 55 people and this study used a questionnaire in data collection. The data analysis technique used is descriptive analysis, validitty and reliability testing, classical assumption test, multiple linear regression analysis, t-test analysis, coefficient of determination, and standardized coefficient beta. The results of the analysis produce a regressio equation model Y = -4.370 + 0.813X1 + 0.333X2. This study resulted in four conclusions, namely (1) there is a partially positive and significant influence of communication on employee morale. (2) there is a partially positive and significant influence of motivation on employee morale. (3) the influence of communication and motivation on employee morale at Disini Luxury Spa And Villas Srminyak is 49,9%. (4) communication is the most dominant variable affecting employee morale at Disini Luxury Spa And Viillas Seminyak with a value of 0.650, while the motivation variable is 0.208.